Green Architecture Approach in Redesign of Popoh Beach Tulungagung Regency - Roy Azwan Saputra; Darmansjah; Benny Bintarjo (Kirana Publisher (KNPub), 2026)
The tourism sector plays a strategic role, yet its potential in Tulungagung Regency has not been fully optimized. Although tourism in Tulungagung has generally recovered in the post-pandemic period, specific destinations such as Popoh Beach have experienced a significant decline in visitors from 18,847 in 2022 to 8,761 in 2024. This condition indicates the urgency of redesigning the area. This study aims to redevelop the Popoh Beach area based on Green Architecture principles by identifying inhibiting factors, determining appropriate design concepts, and formulating a sustainable facility redesign model. The research employs a qualitative approach with data triangulation through literature studies, interviews, and field observations. The expected outcome is a design model focused on reducing carbon footprints through passive design strategies, providing coastal environmental education, and empowering the local economy through integrated zoning arrangements. This redesign is expected to offer a solution to declining visitor numbers while ensuring environmental and economic sustainability in the tourism area.